(untitled) (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2019)
Abstract Among the four components of education, mu’allim is the most important components which significantly influencies the other three components i.e student, subject, method. Mu’allim refers to Allah, whereas Adam and Muhammad became the first and the last students correspondingly. The first three chapters revealed to prophet Muhammad contained four competencies of mu’allim. The objective of this research is not only to redefine the concept of mu’allim, but also to describe various competencies and mu’allim’s role so as to allow its prophetic profession to be more significant in social institution. This research uses descriptive qualitative method with collecting documented data technique on written sources about mu’allim. Since it refers to Allah and prophet Muhammad, the sacrality of mu’allim concept cannot be interpreted merely as a teacher teaching religious study at school. Mastery of spiritual, intellectual, personal, and social competence makes mu’allim status prophetic, just as prophet Muhammad whose role was not limited only as a patron for his children at home and teacher for students at school, but also as social transformer. Since both teacher and lecturer are called mu’allim, therefore, intellectual competency does not only become mandatory to be mastered by lecturers but also by teachers so as to enable them to develop knowledge through scientific publications. Abstrak Di antara empat komponen utama pendidikan, mu’allim merupakan komponen terpenting yang berpengaruh signifikan terhadap tiga komponen lain, yakni murid, materi, metode. Mu’allim merujuk kepada Allah, sedangkan Adam dan Muhammad menjadi murid pertama dan terakhir Allah. Tiga surah pertama yang diwahyukan kepada Nabi Muhammad mengandung empat kompetensi mu’allim. Tujuan penelitian ini tak hanya untuk meredefinisi konsep mu’allim, namun juga untuk mendeskripsikan berbagai kompetensi dan peran mu’allim agar peran profesi profetik itu signifikan di institusi sosial. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik pengumpulan data dokumentasi terhadap sumber tertulis mengenai mu’allim. Karena merujuk kepada Allah dan Nabi Muhammad, sakralitas konsep mu’allim tak cukup diartikan guru yang mengajarkan ilmu agama di sekolah. Penguasaan atas kompetensi spiritual, intelektual, personal, dan sosial membuat status mu’allim menjadi profetis seperti Nabi Muhammad yang tak hanya berperan sebagai pengasuh anak di keluarga dan pengajar murid di sekolah tetapi juga menjadi pentransformasi masyarakat. Karena baik guru maupun dosen disebut mu’allim, maka kompetensi intelektual, sebagai contoh, tak hanya wajib dikuasai dosen, tetapi juga mesti dimiliki guru agar dapat mengembangkan ilmu lewat publikasi ilmiah.